2022
DOI: 10.33218/001c.37505
|View full text |Cite
|
Sign up to set email alerts
|

Ionically Complexed Nanoparticles for Heparin Oral Delivery

Abstract: Ionically complexed nanoparticles were prepared from an anionic polysaccharide drug, heparin, entrapped by a positively charged chitosan polysaccharide. In this study, the encapsulation of heparin was studied to optimize properties needed for its oral drug delivery. Chitosan, used in a variety of biomedical applications, was selected as a cationic polymer for heparin encapsulation. These particles were prepared with a slightly positive charge and an appropriate size for oral drug delivery. The release profiles… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Slightly more positive (+9 mV) chitosan nanoparticles were also prepared by [ 79 ] and investigated for their drug release of plasmid DNA. The study showed complete release in 24 h. More recently, Subramaniam and co-workers [ 80 ] aimed to fabricate chitosan nanoparticles with a charge between +1 and +10 mV for increased cellular penetration. The prepared nanoparticles were +19 mV, and it achieved 70% release of its payload after 4 h at pH 7.2.…”
Section: Discussionmentioning
confidence: 99%
“…Slightly more positive (+9 mV) chitosan nanoparticles were also prepared by [ 79 ] and investigated for their drug release of plasmid DNA. The study showed complete release in 24 h. More recently, Subramaniam and co-workers [ 80 ] aimed to fabricate chitosan nanoparticles with a charge between +1 and +10 mV for increased cellular penetration. The prepared nanoparticles were +19 mV, and it achieved 70% release of its payload after 4 h at pH 7.2.…”
Section: Discussionmentioning
confidence: 99%